2019
DOI: 10.1038/s41598-019-52224-3
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glucose acts directly on osteocytes to increase sclerostin expression in diabetes

Abstract: Bone quality in diabetic patients is compromised, leading to weaker bones and increased fracture risk. However, the mechanism by which this occurs in diabetic bone remains to be fully elucidated. We hypothesized that elevated glucose and glucose variation would affect the function of osteocytes, essential regulators of bone homeostasis and quality. To first test this hypothesis, we used the IDG-SW3 osteocyte-like cell line to examine the effects of glucose levels on osteocyte function and viability in vitro. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 39 publications
(45 reference statements)
2
20
0
2
Order By: Relevance
“…Moreover, T2DM subjects have higher sclerostin levels than patients with T1DM [ 28 , 29 , 30 , 31 ], although this does not seem to be correlated with the risk of T2DM onset [ 27 ]. Preclinical findings also suggest that high glucose levels can directly increase the sclerostin expression leading to a negative impact on bone quality in DM [ 32 ]. Recent clinical data have confirmed that subjects with T2DM have higher bone gene expression of SOST, suggesting that impaired WNT signaling may be one of the key factors impairing bone metabolism in diabetic patients [ 33 ].…”
Section: How Bone Active Therapies Affect Glucose Metabolismmentioning
confidence: 99%
“…Moreover, T2DM subjects have higher sclerostin levels than patients with T1DM [ 28 , 29 , 30 , 31 ], although this does not seem to be correlated with the risk of T2DM onset [ 27 ]. Preclinical findings also suggest that high glucose levels can directly increase the sclerostin expression leading to a negative impact on bone quality in DM [ 32 ]. Recent clinical data have confirmed that subjects with T2DM have higher bone gene expression of SOST, suggesting that impaired WNT signaling may be one of the key factors impairing bone metabolism in diabetic patients [ 33 ].…”
Section: How Bone Active Therapies Affect Glucose Metabolismmentioning
confidence: 99%
“…In support of this notion, the presence of insulin receptors in UMR106-01 cells, not in immature osteoblastic UMR201-10B cells, was previously reported 32 . Similarly, insulin receptor expression was detected in the osteocyte-like cell line IDG-SW3 33 . Despite these findings, in vivo evidence for the expression of insulin receptors in osteocytes is limited.…”
Section: Discussionmentioning
confidence: 86%
“…The important role of both molecules has also been demonstrated in a mouse model, showing that a bispecific antibody targeting sclerostin and DKK-1 supports bone mass accrual and fracture repair, exerting a greater effect compared to monotherapies[ 71 ]. In type 1 diabetic rats, an increased SOST mRNA and sclerostin expression has been observed[ 72 ]. Clinical studies and Homeostatic Model Assessment for Insulin Resistance have shown an inverse correlation between sclerostin and insulin levels, suggesting that sclerostin could modulate glucose homeostasis[ 73 ].…”
Section: Factors Influencing Bone Mass Accrual In T1dm Children and Adolescentsmentioning
confidence: 99%